Don't Forget The Fragment! An Unusual Case of Occult Fragment Embolisation Following Penetrating Neck Injury. Issue 4 (1st December 2011) - Davies, Emma; Boylan, M; Hawker, JJ; Banerjee, B
Abstract : Fragment embolisation following vascular injury is uncommon. The case of a 31 year old soldier, who sustained a penetrating fragment injury to the neck with distal arterial embolisation, is presented and the discussion illustrates both the importance of expedient assessment and management of cervical vascular injuries and of thorough correlation of clinical and radiological findings to avoid missed emboli.